Superresolution imaging of biological nanostructures by spectral precision distance microscopy - Cremer, Christoph; Kaufmann, Rainer; Gunkel, Manuel; Pres, Sebastian; Weiland, Yanina; Müller, Patrick; Ruckelshausen, Thomas; Lemmer, Paul; Geiger, Fania; Degenhard, Sven; Wege, Christina; Lemmermann, Niels A. W.; et al. (Biotechnology journal, 2011)
For the improved understanding of biological systems on the nanoscale, it is necessary to enhance the resolution of light microscopy in the visible wavelength range beyond the limits of conventional epifluorescence microscopy (optical resolution of about 200 nm laterally, 600 nm axially). Recently, various far-field methods have been developed allowing a substantial increase of resolution (“superresolution microscopy”, or “lightoptical nanoscopy”). This opens an avenue to ‘nano-image’ intact and even living cells, as well as other biostructures like viruses, down to the molecular detail. Thus, it is possible to combine light optical spatial nanoscale information with ultrastructure analyses and the molecular interaction information provided by molecular cell biology. In this review, we describe the principles of spectrally assigned localization microscopy (SALM) of biological nanostructures, focusing on a special SALM approach, spectral precision distance/position determination microscopy (SPDM) with physically modified fluorochromes (SPDMPhymod. Generally, this SPDM method is based on high-precision localization of fluorescent molecules, which can be discriminated using reversibly bleached states of the fluorophores for their optical isolation. A variety of application examples is presented, ranging from superresolution microscopy of membrane and cytoplasmic protein distribution to dual-color SPDM of nuclear proteins. At present, we can achieve an optical resolution of cellular structures down to the 20-nm range, with best values around 5 nm (∼1/100 of the exciting wavelength).
Gesehen am 21.04.2022